Last-line local treatment with the Quad Shot regimen for previously irradiated head and neck cancers. (May 2020) - Fan, Dan; Kang, Jung J.; Fan, Ming; Wang, Huili; Lee, Anna; Yu, Yao; Chen, Linda; Jillian Tsai, C.; McBride, Sean M.; Riaz, Nadeem; Gelblum, Daphna Y.; Neal, Brian P.; et al.
Highlights: QS is an effective palliative therapy in patients with previously irradiated HNC. Administration of 3–4 QS cycles predicts palliative response and improved survival. Proton therapy has potential survival benefits in the palliative re-RT setting. Abstract: Objectives: Patients with prior irradiated head and neck cancer (HNC) who are ineligible for definitive retreatment have limited local palliative options. We report the largest series of the use of the Quad Shot (QS) regimen as a last-line local palliative therapy. Materials and Methods: We identified 166 patients with prior HN radiation therapy (RT) treated with QS regimen (3.7 Gy twice daily over 2 consecutive days at 4 weeks intervals per cycle, up to 4 cycles). Palliative response defined by symptom(s) relief or radiographic tumor reduction, locoregional progression free survival (LPFS), overall survival (OS) and radiation-related toxicity were assessed. Results: Median age was 66 years. Median follow-up for all patients was 6.0 months and 9.7 months for living patients. Overall palliative response rate was 66% and symptoms improved in 60% of all patients. Predictors of palliative response were > 2 year interval from prior RT and 3–4 QS cycles. Median LPFS was 5.1 months with 1-year LPFS 17.7%, and median OS was 6.4 months with 1-year OS 25.3%. On multivariate analysis, proton RT, KPS > 70, presence of palliative response and 3–4 QS cycles were associated with improved LPFS and improved OS. The overall Grade 3 toxicity rate was 10.8% (n = 18). No Grade 4–5 toxicities were observed. Conclusion: Palliative QS is an effective last-line local therapy with minimal toxicity in patients with previously irradiated HNC. The administration of 3–4 QS cycles predicts palliative response, improved PFS, and improved OS. KPS > 70 and proton therapy are associated with survival improvements.